Vanadium pentoxide cathode materials for high-performance lithium-ion batteries enabled by a hierarchical nanoflower structure via an electrochemical process - Tang, Yuxin (2013)
Hierarchical vanadium oxide nanoflowers (V10O24·nH2O) were synthesized via a simple, high throughput method employing a fast electrochemical reaction of vanadium foil in NaCl aqueous solution, followed by an aging treatment at room temperature. During the electrochemical process, the anodic vanadium foil is dissolved in the form of multi-valence vanadium ions into the solution, driven by the applied electrical field. After being oxidized, the VO2+ and VO2+ ions instantly react with the OH− in the electrolyte to form uniformly distributed vanadium oxide nanoparticles at a high solution temperature due to the exothermic nature of the reaction. Finally, nucleation and growth of one dimensional nanoribbons takes place on the surface of the nanoparticles during the aging process to form unique hierarchical V10O24·nH2O nanoflowers. Upon heat treatment, the hierarchical architecture of the vanadium pentoxide nanoflower morphology is maintained. Such a material provides porous channels, which facilitate fast ion diffusion and effective strain relaxation upon Li ion charge–discharge cycling. The electrochemical tests reveal that the V2O5 nanoflowers cathode could deliver high reversible specific capacities with 100% coulombic efficiency, especially at high C rates (e.g., 140 mAh g−1 at 10 C).